Suppression of The Torsional Irregularity of High-rise Buildings Using Viscous Wall Dampers - Dilsiz, Abdullah; Özuygur, Ali Ruzi (Springer, 2022)
The energy dissipation devices, with their capabilities of seismic demand reduction, are effective and widely used innovative structural solutions for the seismic protection of buildings. Viscous Wall Dampers (VWD) are also encouraging for new design opportunities of high-rise buildings such as reinforced concrete (RC) special moment resisting frames (SMRF). Moreover, retrofitting the existing buildings with VWDs is also possible without any detrimental effects on the architectural design. This study investigates the effectiveness of VWDs on the dynamic performance of high-rise buildings having torsional irregularity. A 22-story irregular RC SMRF building is designed and subjected to a seismic redesign process equipping the building only with VWDs, without changing the dimensions of any other structural elements. The VWDs are placed to suppress the torsional irregularity of the basic design for seismic mitigation objectives. The seismic performances of the buildings with various configurations of VWDs are evaluated. The location of the prototype building is selected to be in a highly seismic active area in Turkey. A readily available and validated computational model for VWD is implemented. The results of the nonlinear response history analysis (NRHA) have shown that the wall dampers can effectively reduce the torsional irregularity, as well as the maximum interstory drift ratios to less than 2% which is set as the target performance objective for the design-based earthquake level. By installing VWDs, it is demonstrated that the torsional irregularity is suppressed while the flexible SMRF design for a 22-story building still satisfies the target performance objectives.
Keywords: Wall Dampers; Torsional Irregularity; Seismic Design; Special Moment Resisting Frames; Reinforced Concrete; Nonlinear Response History Analysis